ANALISIS TINGKAT PELAYANAN STASIUN LEMPUYANGAN TERHADAP KEPUASAN PENGGUNA JASA DENGAN INTEGRASI METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN MODEL KANO - , KOMANG SWANITA R. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Excellent service is one of the targets of PT. Kereta Api Indonesia (Persero), but complaints are still found from service users about the train service at the station. The aim of this study is to maximize efforts in service innovation in Lempuyangan Station and service indicator to know that the main priority to be improved. Importance Performance Analysis (IPA) techniques which are integrated to Kano Model was used for increased performance attributes are not always proportional to the increase in customer satisfaction, then a research was done in Lempuyangan Station Yogyakarta by integrating IPA and Kano Model. The main priority for the enhanced attributes are determined by the difference between perception and expectation scores after integrating IPA and Kano models also providing suggestions for improvement in order to meet the expectations of service users. Characteristics of service users is the percentage of gender, level of education, employment and travel destinations. CSI value of 66% means that the level of satisfaction of the service users is categorized as âsatisfiedâ with the services in Lempuyangan Station. There are, one for each attributes that are categorized as âmust beâ and âattractiveâ. Six attributes are prioritized to be improved in quadrant one and belong to one dimensional category. After conducting a gap analysis, it is known that the attribute âeasy and fast ticket purchasesâ becomes the most important priority for repair.